A machine-readable online database for rate coefficients in radical polymerization - Van Herck, Joren; Harrisson, Simon; Hutchinson, Robin A; Russell, Gregory T; Junkers, Tanja (Polymer chemistry, 2021)
An online database created and curated by an IUPAC subcommittee is introduced. It is designed to act as a central access point for finding reliable kinetic data on radical polymerizations. The database can be accessed via a webinterface or via Python code available for download, and at the moment consists mostly of propagation rate coefficient data. Expansion to other coefficients, and eventually also other types of polymerization, is anticipated in time. Monomers can be searched by name, CAS number, SMILES notation or their InChI and InChiKey descriptors. The database returns values for Arrhenius parameters for the chosen reaction, key information for measurement conditions, and information as to whether the respective value has been subject to benchmarking by IUPAC. The aim of the database is to simplify the search for coefficients, and to unify modelling approaches in the community. Further, since the database is designed to be fully machine-readable, it allows for direct integration into software code, which enables advanced machine-learning and other computer-based research. An online database created and curated by an IUPAC subcommittee is introduced.